Fructooligosaccharide and application in dairy products: a literature review (Research, Society and Development, 2023)
Fructooligosaccharide (FOS) is one of the most relevant prebiotics in the food industry, in addition to contributing to the sensory characteristics of the product, it also confers benefits to the health of the host. The effect of FOS is often associated with its beneficial effects on the intestinal microbiota. This study aims to conceptualize fructooligosaccharides in terms of definition, innovation, trends, impact on health and application in dairy products through an integrative literature review. Experimental and non-experimental studies were used to have a complete understanding of the proposed theme. The search was performed on the ScienceDirect database and was restricted to open access studies published in the last five years using “fructooligosaccharides”, “FOS”, “healthy”, “dairy”, “milk” as keywords. The study provides evidence on the origin, innovation, trends, impact on health of fructooligosaccharides, thus proving their relevance and functionality in the food industry, mainly due to the current focus on functional foods. Therefore, the addition of fructooligosaccharides in dairy products is feasible, which leads to the search for innovation and updating of formulations, associating it with other beneficial substances for greater efficiency in nutritional, sustainable and economic terms.